1991
DOI: 10.1002/nml.4130020206
|View full text |Cite
|
Sign up to set email alerts
|

How nonprofit human service organizations manage their funding sources: Key findings and policy implications

Abstract: Major findings and policy implications on how nonprofit social service organizations manage their funding relations are summarized. Data from in-depth case studies of six medium-sized social service organizations with distinctive funding profiles yielded findings on the major contingencies associated with controlling fees, the volatility of donations, and the driving force of public funding relationships for funders (public and private), nonprofit managers, and the role of nonprofit organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 15 publications
0
59
0
1
Order By: Relevance
“…However, while these organizations are free from specific allocation demands associated with government or foundation grants, it has been argued that commercial activity compromises the independence and strategic integrity of the agency. Gronbjerg (1991), for example, reported that agencies drawing significant commercial income were more likely to raise concerns regarding mission or goal displacement, and as Froelich (1999) argued, ". .…”
Section: Financial Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, while these organizations are free from specific allocation demands associated with government or foundation grants, it has been argued that commercial activity compromises the independence and strategic integrity of the agency. Gronbjerg (1991), for example, reported that agencies drawing significant commercial income were more likely to raise concerns regarding mission or goal displacement, and as Froelich (1999) argued, ". .…”
Section: Financial Sourcesmentioning
confidence: 98%
“…Private contributions to nonprofits, for example, have generally been declining as a percentage of total revenue since 1964 (Weisbrod, 1998), and government allocation of funding tends to fluctuate with changes in political leadership and public policy (Froelich, 1999). As business development and survival strategies within for-profit organizations are dependent on the nature and uniqueness of a firm's resources (Pfeffer and Salancik, 1978), strategic decisions by nonprofit CEOs depend on the stability and nature of the organization' s funding (Gronbjerg, 1991).…”
mentioning
confidence: 99%
“…Compared with competing for a shrinking pool of government funds, obtaining private funding may involve lower transaction costs, and less administration (Gronbjerg 1991;Kramer 1994). Philanthropic funding has been celebrated for being flexible and risk-tolerant, and free from the 'hindrance' of accounting to shareholders or voters (Anderson 2013).…”
Section: Strengths and Limits Of Private Fundingmentioning
confidence: 99%
“…The relations between nonprofits and their funders are good examples of this. Indeed, several studies have already documented the tension between the more social orientation of nonprofits and the often more economic orientation of funders (Battilana and Dorado 2010;Chahine and Tannir 2010;Chew and Osborne 2008;Gronbjerg 1991Gronbjerg , 1993, a tension that occurs even in single-sectoral collaborations, on account of certain withinsector organizations becoming more ''corporatized'' than others (Selsky and Parker 2010). Relations between nonprofits and their funders can legitimately be viewed as collaborations rather than exchanges, as even when such relations are thought to be primarily transactional (Austin 2000), they are nevertheless characterized by more than C. Cloutier, A. Langley just a simple exchange of money (Googins and Rochlin 2000;Jamali and Keshishian 2009).…”
Section: Collaboration and Struggles Over Purposementioning
confidence: 99%